1961
DOI: 10.1099/00221287-26-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Factor I and Recognition of a Third Factor of the Anthrax Toxin

Abstract: SUMMARYFactor I of the anthrax toxin was isolated and showed one major component in the ultracentrifuge and on paper electrophoresis; it contained less than 5.5% of extraneous antigens detectable by serological precipitation in gels. The final preparation contained all the usual amino acids (N = 10*1%) and some carbohydrate (6 yo, calculated as glucose) and phosphorus (0.7 yo). The most striking aspects of its analysis were a high ash (10-13y0) and a light absorption a t 260 mp. The high ash was not due to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
144
1
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 4 publications
4
144
1
1
Order By: Relevance
“…These acute effects might be expected to mask any cAMP-mediated responses. In the only studies directly implicating EF as a virulence factor, mice were found to be killed by lower doses ofthe lethal toxin (PA and LF) when EF was administered simultaneously (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These acute effects might be expected to mask any cAMP-mediated responses. In the only studies directly implicating EF as a virulence factor, mice were found to be killed by lower doses ofthe lethal toxin (PA and LF) when EF was administered simultaneously (4).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments involving sequential injections of PA and LF led to the hypothesis that the factor common to both activities, PA, binds to tissue receptors and permits subsequent action of either LF or EF (6). This model was supported by the demonstration that LF blocks the action of EF (4).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Each is composed of a common binding component, protective antigen (PA), 1 together with an enzymatic component, edema factor (EF), in the case of edema toxin and lethal factor (LF) in the case of lethal toxin (1)(2)(3). The current model for toxin entry into the cell illustrates the centrality of PA for toxin action.…”
mentioning
confidence: 99%
“…Harry Smith published notable contributions to the study of bacterial pathogenesis in the journal, with studies on Bacillus anthracis, Brucella, and Neisseria gonorrhoeae (Smith, 1990). These included several papers on the purification and characterization of the tripartite anthrax toxin and the use of in vivo grown bacilli to facilitate toxin purification (Smith & Stanley, 1962;Stanley & Smith, 1961, 1963Stanley et al, 1960). Smith was already convinced in 1947 that 'to learn more about bacterial pathogenicity we should examine organisms grown in vivo' (Smith, 1990) -a concept that has truly come to fruition with modern tools in cellular and molecular biology.…”
mentioning
confidence: 99%